Rapid composition screening for perovskite photovoltaics via concurrently pumped ultrasonic spray coating. Issue 10 (15th February 2016) - Tait, J. G.; Manghooli, S.; Qiu, W.; Rakocevic, L.; Kootstra, L.; Jaysankar, M.; Masse de la Huerta, C. A.; Paetzold, U. W.; Gehlhaar, R.; Cheyns, D.; Heremans, P.; Poortmans, J.
Abstract : Concurrently pumped ultrasonic spray coating is implemented for rapid composition screening and in situ bandgap control of perovskite photovoltaics, achieving 15.7% efficiency for devices and 11.7% for modules, and tested under continuous maximum power point tracking. Abstract : Transitioning perovskite photovoltaics from the rapid progress in lab-scale devices to industrially viable large area modules is a key challenge for the economic breakthrough of the technology. In this work, we demonstrate ultrasonic spray coating as a scalable and versatile linear deposition technique for high efficiency perovskite photovoltaics. We show the versatility of concurrently pumped ultrasonic spray coating by rapidly and precisely optimizing precursor ratios based on PbCl2, Pb(CH3 CO2 )2 ·3H2 O, PbBr2, CH3 NH3 Br, and CH3 NH3 I to achieve highly crystalline and pinhole-free layers. Initial power conversion efficiencies of 15.7% for small scale devices and 11.7% for 3.8 cm 2 modules were achieved with current–voltage sweeps and tracked to 13.4% for devices and 10.4% for modules under continuous illumination and bias at the maximum power point. Process versatility is further demonstrated with the in situ bandgap control in CH3 NH3 PbI X Br3− X layers.